Effect Of Mocaf Flour Substitution On Kastengel Cookies Quality - Fadiah, Meutia; Syarif, Wirnelis (Universitas Negeri Padang, 2022)
Kastengel in Dutch is kaas which means cheese and stengel which means stem are pastries or cookies with a rectangular shape with a length of about 4.5 cm, a width of 1 cm and a height of 0.8 cm made of wheat flour dough as the main ingredient. The use of wheat flour is still a lot, and the development of flour production using local food such as modified cassava is known as mocaf. This study discusses the quality (shape, color, aroma, texture and taste) of kastengel substitution of mocaf flour as much as 25%, 50% and 75%. This type of research is a pure experiment with Completely Randomized Design (CRD) method. The data used is data obtained directly by 3 expert panelists who provide answers from the questionnaire (organoleptic test format). The data obtained was then tabulated in the form of a table and then carried out Analysis of Variance (ANOVA). If the analysis of variance shows that Fcount > Ftable, then it is continued with Duncan's test. The results of this study indicate that there is no significant effect on the quality of shape, color, aroma, texture and taste of kastengel substitution of mocaf flour. The best quality of mocaf flour substitution was in treatment (X1) with 25% mocaf flour substitution.